Cultura e(m) telecolaboração: uma análise de parcerias de teletandem institucional - Zakir, Maisa de Alcântara [UNESP] (2015)
This dissertation presents an exploratory ethnographic study that investigates telecollaborative partnerships among students of a public university in Brazil and of a private university in the United States. The research study is part of the project entitled Teletandem: Transculturality in Online Communication in Foreign Languages via Webcam and is related to the topic ways of understanding the partner's culture and its impacts on the learning process and the relationship between partners. The study aims at investigating the role of culture in the context of an institutional teletandem partnership. Thus, the specific objectives are: identifying the participants' conceptions of culture in activities proposed in a virtual learning platform and understanding how culture emerges in the dynamics of teletandem interactions. The participants were in contact with each other during part of the spring semester of 2012 in ten interactions conducted via Skype, with audio, video and chat resources. The last five teletandem sessions were recorded and the transcriptions are the main data of this study. Besides the interactions, other activities are part of the corpus: (a) texts that were written and published by the students in a virtual learning platform (user's profile; narratives about the teletandem interactions; posts in a virtual discussion forum) and (b) handwritten texts that were produced by the students of the American university at the end of the semester. Considering the principle of dialogism from the relationality of the self and the other, and the production of meaning as part of the social activities of students, data are interpreted under the perspective of the theoretical methodological principles of what is called in Brazil Dialogic Discourse Analysis. Thus, the different texts produced by the participants will be deemed to give more elements to interpret data and, therefore, to investigate linguistic, social and ...